Financial problems and delinquency in adolescents and young adults: a 6-year three-wave study - Hoeve, Machteld (Crime & delinquency, 2016)
The present study examined the link between financial problems and delinquency in adolescents and young adults (N = 1,258). Using three measurement waves that covered a time span of 6 years, we conducted cross-lagged panel analyses. Overall, we found evidence that financial problems increase the risk of delinquency, and vice versa. Effects of delinquency on financial problems were larger than the other way around. In addition, a longer term (6 year) effect of delinquency on financial problems was found, whereas this effect was not found for financial problems to delinquency. Gender and age did not moderate the financial problem–delinquency link, suggesting that the bidirectional effect between financial problems and delinquency applies to adolescent and young adult males and females. Finally, we found some evidence to suggest that the indirect effects became stronger over time.